PREDIKSI FINANCIAL DISTRESS : RASIO KEUANGAN DAN SENSITIVITAS MAKROEKONOMI PERUSAHAAN SEKTOR PRIMER - Sumani Sumani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2019)
ABSTRACTThe objective of this research is to analyze the ability of macroeconomic proxied by the sensitivity of exchange rate and interest rate, and the ability of financial ratios proxied by current ratio (CR); return on assets (ROA); total asset turnover (TATO); debt to asset ratio (DAR); and sales growth (GROWTH), in predicting financial distress in primary sector companies in Indonesia. The population was 42 primary sector companies in Indonesia from the agricultural sector and mining sector listed on the Indonesia Stock Exchange. By employing a purposive sampling technique, the sample consisted of 39 companies, i.e., 9 agricultural companies and 30 mining companies in the 10 years range of the study from 2008 to 2018. Data were analyzed using logistic regression analysis. Results showed that ROA and DAR variables can be used to predict a company's financial distress. However, the exchange rate variable proxied by exchange rate sensitivity, interest rate variable proxied by interest rate sensitivity, CR, TATO, and GROWTH cannot be used to predict financial distress.Keywords: financial distress, financial ratio, and sensitivity of macroeconomc